Investigation of soil quality (health) in commercial production of rooibos tea (Aspalathus linearis) in the Western Cape, South Africa - Smith, Jacobus Francios Naude (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.